2017
DOI: 10.1101/231464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient topographical dynamics of the electroencephalogram predict brain connectivity and behavioural responsiveness during drowsiness

Abstract: 8As we fall sleep, our brain traverses a series of gradual changes at physiological, behavioural and 9 cognitive levels, which are not yet fully understood. The loss of responsiveness is a critical event in 10 the transition from wakefulness to sleep. Here we seek to understand the electrophysiological 11 signatures that reflect the loss of capacity to respond to external stimuli during drowsiness using two 12 complementary methods: spectral connectivity and EEG microstates. Furthermore, we integrate 13 these … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 74 publications
4
20
0
Order By: Relevance
“…Chennu et al highlighted that the re-emergence of behavioral awareness is correlated with the fronto-parietal alpha band wPLI connectivity. In addition, other studies showed that a decrease in the posterior-anterior alpha band’s wPLI connectivity was associated with the transition into unconsciousness due to sedation or sleep [ 29 , 30 , 31 ]. Based on these previous results, and considering our findings showing that wPLI connectivity in the alpha band was decreased in the sham and increased in the active sessions (which led to a significant increase in fronto-parietal alpha band connectivity), we may argue that anodal tDCS deprived patients of drowsiness in the active session.…”
Section: Discussionmentioning
confidence: 99%
“…Chennu et al highlighted that the re-emergence of behavioral awareness is correlated with the fronto-parietal alpha band wPLI connectivity. In addition, other studies showed that a decrease in the posterior-anterior alpha band’s wPLI connectivity was associated with the transition into unconsciousness due to sedation or sleep [ 29 , 30 , 31 ]. Based on these previous results, and considering our findings showing that wPLI connectivity in the alpha band was decreased in the sham and increased in the active sessions (which led to a significant increase in fronto-parietal alpha band connectivity), we may argue that anodal tDCS deprived patients of drowsiness in the active session.…”
Section: Discussionmentioning
confidence: 99%
“…Transition of consciousness in the near-awake to light-decrease of alertness is emerging as a model for internally caused interactions (Canales-Johnson et al;Comsa et al, 2019;Noreika et al;Song and Tagliazucchi, 2020;Tagliazucchi and Laufs, 2014) . With lesion and pharmacological challenges, neuropsychology and cognitive neuroscience have tried to define the necessary and sufficient brain networks, areas and dynamics of the brain to implement cognition, revealing compensation, reconfiguration and plasticity (Adolphs, 2016;Valero-Cabré et al, 2017;Yeung et al, 2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the patient's hdEEG network evolved over many months of repeated assessments, and we observed the presence of increased frontoparietal connectivity at the 6th assessment, in keeping with an increased CRS-R score and behavioral evidence of consciousness. Broadly speaking, there is considerable evidence linking the presence of robust frontoparietal alpha networks with conscious awareness, from research into other altered states, including sleep ( 37 ) and sedation ( 19 , 38 ) in particular. That hdEEG metrics derived from alpha connectivity can track fine-grained longitudinal changes in behavioral state of an individual pDOC patient, even after a long intervening period since the original brain injury (7 years in case of Patient 1), is valuable new knowledge that speaks to the clinical utility of repeated hdEEG network assessments of consciousness.…”
Section: Discussionmentioning
confidence: 99%